Antagonist’s Language in The Jakarta Post Editorial: Appraisal Critical Discourse Analysis - Salsabilla, Fissilmi; Prasiyanto Cahyono, Setyo (Universitas Muhammadiyah Semarang, 2024)
This study explores the antagonist’s language in representing his arguments in the Jakarta Post editorial. The sources of data of this study were gained from the Editorial of The Jakarta Post newspaper which were published in February 2024. The data were collected purposively by choosing five out of twenty-seven editorials. In conducting this study, the researchers employ descriptive qualitative method to describe the language phenomenon used by the journalist in representing their arguments. Meanwhile, the theoretical framework of Appraisal theory used in this study was proposed by Martin and Rose (2007). Furthermore, in analyzing the data content analysis is used to analyze the data. The findings of this study reveal that the distinctive patterns of appraisal expression in the editorial is reflecting the antagonist’s perspectives and ideological orientation. The analysis highlights the role of language by the journalist can influence readers' attitudes, beliefs, and worldviews within the socio-political context through. The exploitation of attitude appraisal indicates that the journalists share their thoughts and opinions firmly. Meanwhile, the use of engagement is to positioned themselves in the arguments they delivered and the application of graduation is to strengthen their arguments.